Analisis Penjadwalan Percepatan Proyek Outfitting Machinery Blok ASA 2A S Pada Pembuatan Kapal A Menggunakan Microsoft Project dengan Precedence Diagram Method di PT. XYZ - Aryaduta, Galang; Farida Pulansari (Jurnal Serambi Engineering, 2025)
The shipbuilding project is highly complex, involving multiple phases and interdependent activities with extended durations. One of the main challenges in this project is how to design an effective schedule to minimise the completion time without compromising the quality of work. The objective of this study is to analyse the project acceleration of the Machinery Outfitting of Block ASA 2A S of the A Ship at PT. XYZ using Microsoft Project software and the Precedence Diagram Method (PDM). The research process began with the collection of data on job sequences, activity durations and dependencies between activities. This data was processed using PDM to identify the critical path, which consisted of eight main activities: A, B, D, E, G, H, K and M. Through critical path analysis, rescheduling was carried out to accelerate project completion. The results show that the project duration was successfully reduced from the original plan of 61 days to 54 days, enabling PT. XYZ to complete the machinery outfitting of Block ASA 2A S on the A Ship project by 1 September 2020. This improvement increased time and cost efficiency without compromising project quality. This study demonstrates the effectiveness of using Microsoft Project with PDM to manage complex project schedules.